Click chemistry connections for functional discovery - Finn, M. G; Kolb, Hartmuth C; Sharpless, K. Barry (Nature Synthesis, 2022)
The organizing principles of click chemistry help scientists make molecules for a variety of applications. Such democratization of synthesis is challenging and rewarding, as useful simplicity is difficult to achieve. We reflect on this and look forward, hoping to continue to tie the joy of functional discovery to the challenges of synthetic chemistry.